Filtering Based Illumination Normalization Techniques for Face Recognition - Sasan Karamizadeh; Shahidan M abdullah; Seyed Mohammad Cheraghi; MazdakZamani MazdakZamani (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The main challenge experienced by the present face recognition techniques and smooth filters are the difficulty in managing illumination. The differences in face images that are created by illumination are normally bigger compared to the differences in inter-person that is utilized to differentiate identities. However, face recognition over illumination has more uses in a lot of applications that deal with subjects that are not cooperative where the highest potential of the face recognition as a non-intrusive biometric feature can be executed and utilized. This study aims to offer a crucial review of researches involving illumination techniques, and image-based face recognition over illumination. Information was collected from journals, books and electronic sources published in the period of 1971 to 2013. In depth explanation is provided on the advantages and drawbacks, strategies and performance levels of the current techniques. DOI: http://dx.doi.org/10.11591/telkomnika.v13i2.7001